Isotopic and spin-nuclear effects in solid hydrogens - Freiman, Y.A.; Yanier Crespo (Физика низких температур, 2018)
The multiple isotopic family of hydrogens (H₂, HD, D₂, HT, DT, T₂) due to large differences in the de Boer quantum parameter and inertia moments displays a diversity of pronounced quantum isotopic solid-state effects. The homonuclear members of this family (H₂, D₂, T₂) due to the permutation symmetry are subjects of the constraints of quantum mechanics which link the possible rotational states of these molecules to their total nuclear spin giving rise to the existence of two spin-nuclear modifications, ortho- and parahydrogens, possessing substantially different properties. Consequently, hydrogen solids present an unique opportunity for studying both isotope and spin-nuclear effects. The rotational spectra of heteronuclear hydrogens (HD, HT, DT) are free from limitations imposed by the permutation symmetry. As a result, the ground state of these species in solid state is virtually degenerate. The most dramatic consequence of this fact is an effect similar to the Pomeranchuk effect in ³He which in the case of the solid heteronuclear hydrogens manifests itself as the reentrant broken symmetryphase transitions. In this review article we discuss thermodynamic and kinetic effects pertaining to different isotopic and spin-nuclear species, as well as problems that still remain to be solved.